An efficient inductor-capacitor-inductor-capacitor compensation topology for wireless power transfer system - Irshad, Talha; Nauman, Malik; Emeroylariffion Abas, Pg (Bulletin of Electrical Engineering and Informatics, 2025)
Wireless power transfer (WPT) systems provide a promising alternative for charging various applications, including electric vehicles (EVs), biomedical implants, smartphones, and network sensors. However, these systems often struggle to maintain high efficiency under varying loading and coupling conditions. This paper addresses these challenges by proposing a novel hybrid inductor-capacitor-inductor-capacitor (LC-LC) compensation topology. The proposed LC-LC topology is specifically designed to outperform conventional single-element compensation topologies, such as series-series (SS) and series-parallel (SP) configurations, by effectively reducing leakage inductance between coils. An analytical model of the LC-LC topology is developed and validated through simulations using Keysight advanced design system (ADS) software. The results demonstrate that the LC-LC topology not only achieves a peak efficiency of 99.6% under optimal conditions but also maintains superior performance compared to SS and SP topologies, with only a slight decrease to 93% efficiency observed at low load resistances. These findings highlight the potential of the LC-LC topology to significantly enhance WPT system efficiency across a range of operating conditions.